Wittgenstein's Philosophical investigations : text and context - Arrington, Robert L., 1938-2015; Glock, Hans-Johann, 1960- (Routledge, 1991)
Although there is a vast amount of secondary literature on the Philosophical Investigations, comparatively little exists which adduces exegetical arguments in favour of particular readings of specific passages. The seemingly disjointed structure of the book has often been taken as a licence to interpret its passages out of context, and there has been a tendency to plunge immediately into discussions about their tenability. In this collection, distinguished Wittgenstein scholars approach the Investigations with the conviction that careful consideration of text and context is needed prior to pronouncements being made on the philosophical significance of individual remarks. Diverse exegetical approaches are represented: while some believe that the Investigations can be read as an independent text, others maintain it is essential to look at the context of a particular remark or variations on it in Wittgenstein's other texts. The authors also differ in their assessment of the philosophical value of their material. Some try to show that careful interpretation reveals valuable insights in what are prima facie untenable passages. Others conclude that certain remarks fail to resolve the issues they address. This is the first strictly exegetical collection of papers on the Investigations, and it fulfils a task no commentary could by exhibiting different interpretive strategies in application to paradigmatic trouble-spots. Therefore it is a major contribution to the understanding of the Investigations and of Wittgenstein's thought in general. It is essential and fascinating reading for those who are interested in this important strand of twentieth-century philosophy.